Walisongo dalam Babad Tanah Jawi dan Relevansinya terhadap Sejarah Geneologi KH Raden Wangsadirana - Dede Nur Zaman; Muhammad Resky (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2026)
Walisongo are known as prominent figures in the spread of Islam in Java, popular in both oral traditions and classical manuscripts such as Babad Tanah Jawi and Babad Gresik I, while studies on their relevance to the genealogy of local religious figures such as KH Raden Wangsadirana remain limited. This study aims to describe the discourse on the genealogy of Walisongo based on a comparative analysis of the Ahla al-Musamarah and Tarikh al-Auliya' books, to analyze the figures of Walisongo in Babad Tanah Jawi and Babad Gresik I, as well as to trace and reconstruct the genealogy of KH Raden Wangsadirana and its relevance to the history of Walisongo. This research employs a qualitative approach using content analysis methods. The primary data sources are Babad Gresik I (Codex LOr No. 6780), Babad Tanah Jawi, as well as the Ahla al-Musamarah and Tarikh al-Auliya' books. Data collection was conducted through bibliographic studies, while data analysis used an integrative and conceptual approach to identify latent messages. The study finds that Walisongo in Babad Tanah Jawi not only served as disseminators of Islam but also as agents of political and cultural change during the transition from Majapahit to Demak. Genealogically, there are similarities and differences between the Ahla al-Musamarah and Tarikh al-Auliya' books regarding lineage order, names of figures, and the origin of Raden Patah's mother (Chinese vs. Campa). Nevertheless, both books agree that the walis are descendants of the Prophet Muhammad SAW. The genealogy of KH Raden Wangsadirana traces back to Sultan Hadiwijaya (Jaka Tingkir), Walisongo, and Prophet Muhammad SAW through the lineage of Syekh Jumadil Kubro. This research reinforces the understanding that the local history and genealogy.